Political Perspective on Attitude and Behavior of National Population towards Voting: The role of social recreation in understanding political attitudes and behavior (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The fundamental conceptual challenge was to capture the traditional demeanor idea as well as the full idea of mentality quality. This required to join diverse hypothetical methodologies and to move all into a scientific and modeling system. The political frames of mind inside a system of artificial natives were picked as explicit application territory where a lot of empirical information is accessible. The paper demonstrates the capability of social recreation to help the blend of various hypothetical methodologies. The reconciliation inside a model shows gaps and inconsistencies and permits formulating theories for further empirical examinations. The model has a measured structure and gives a rich store to different modelers who expect to create models on comparable topics.